The effect of workplace stretching exercise to reduce musculoskeletal complaints in weavers - Maksuk Maksuk; Sherli Shobur; Mardiani Mardiani; Elisa Elisa (Universitas 'Aisyiyah Yogyakarta, 2022)
Weavers often feel musculoskeletal complaints due to the work position that is not ergonomic and is always in a static position for a long time every day. The objective study analyzed the effectiveness of physical stretching at work in reducing musculoskeletal complaints in weavers. This research was a quasi-experiment study with control group pre-test and post-test design. The samples were a total population of as many as 44 weavers (22 as the treatment group and 22 as group control. This study was conducted from October 2019 to December 2020 at Weaving Industry Center “Tuan Kentang“ in Palembang City. Data was collected using a questionnaire be equipped Nordic Body Map. The Wilcoxon test analyzed data. The intervention was a Workplace Stretching Exercise muscle pain scale measured before and after exercise in the treatment group. The average pain level of musculoskeletal complaints in the control and treatment groups was mild to moderate. From the results of the Wilcoxon test, it appears that the value of sig (2-tailed) in the treatment group (0.005) the value of sig (2-tailed) in the control group (0.06), so it can be stated that stretching exercises at work are carried out two times daily for one month is effective to reduce complaints of musculoskeletal pain. Workplace Stretching Exercises effectively reduce musculoskeletal complaints, especially in weavers with static work positions and working for long periods. Stretching exercises can reduce musculoskeletal complaints about traditional weavers if done regularly.